PENGARUH KONVERGENSI IFRS EFFEKTIF TAHUN 2012, KOMPLEKSITAS AKUNTANSI DAN PROBABILITAS KEBANGKRUTAN PERUSAHAAN TERHADAP TIMELINESS DAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Windy Ayu Wulandari; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2015)
This study aimed to examine the effect of IFRS convergence effective in 2012, accounting complexity, and bankruptcy probability on timeliness and earningsmanagement. The sample was manufacturing companies listed in Bursa Efek Indonesia(BEI) that conducted in 2011-2012 as many 224 companies with a sampling technique is using purposive sampling method..Using multiple regression random effects, this study found that the convergence of IFRS effective 2012 and accounting complexity does not affect the timeliness and earnings management. This study also found that bankruptcy probability extend audit delay and submission of financial statements, and also bankruptcy probability reduce the level of earnings management.Kata Kunci:  Konvergensi IFRS Efektif Tahun 2012, Kompleksitas Akuntansi,Probabilitas Kebangkrutan Perusahaan, Timeliness, Manajemen Laba.